A genome-wide association study for malignant mesothelioma risk - Cadby, G.; Mukherjee, S.; Musk, A.; Reid, A.; Garlepp, Michael; Dick I.; Robinson, C.; Hui, J.; Fiorito, G.; Guarrera, S.; Beilby, J.; Melton, P.; et al. (Elsevier, 2013)
Malignant mesothelioma (MM) is a uniformly fatal tumour of mesothelial cells. MM is caused by exposure to asbestos however most individuals with documented asbestos exposure do not develop MM. Although MM appears to aggregate within families, the genetics of MM susceptibility is a relatively unexplored area. The aim of the current study was to identify genetic factors that contribute to MM risk. A genome-wide association analysis of 2,508,203 single nucleotide polymorphisms (SNPs) from 428 MM cases and 1269 controls from Western Australia was performed. Additional genotyping was performed on a sample of 778 asbestos-exposed Western Australian controls. Replication of the most strongly associated SNPs was undertaken in an independent case–control study of 392 asbestos-exposed cases and 367 asbestos-exposed controls from Italy. No SNPs achieved formal genome-wide statistical significance in the Western Australian study. However, suggestive results for MM risk were identified in the SDK1, CRTAM and RASGRF2 genes, and in the 2p12 chromosomal region. These findings were not replicated in the Italian study, although there was some evidence of replication in the region of SDK1. These suggestive associations will be further investigated in sequencing and functional studies.